Studying Judaism : the Critical Issues. - Wright, Melanie J. (Studying world religions., 2012)
This volume in the Studying World Religions series is an essential guide to the study of Judaism. Clearly structured to cover all the major areas of study, including historical foundations, scripture, worship, society, material culture, thought and ethics, this is the ideal study aid for those approaching Judaism for the first time. Studying Judaism offers readers the chance to engage with a religious tradition as a diverse, living phenomenon. Its approach is ''critical'' in two major respects: its use of the dimensional approach to the study of religions as an interpretive framework, and its.